Customer Satisfaction Strategy Through Service Quality and Price Based on the Business Model Canvas: A Study of Warung Barokopi in Menganti District - Al Mubarrok, Alvian Dzaky; Kurniawan, Aries; Panji, Putra; Komara, Beni; Kwarazmita, Tsabita (Journal of Management and Social Sciences, 2026)
This study aims to analyze customer satisfaction strategies related to service and price at Warung Barokopi in Menganti District using the Business Model Canvas (BMC) approach. The study is motivated by the increasing competition among local culinary businesses, particularly coffee shops, where competitiveness is no longer determined only by product quality but also by service performance, price fairness, place comfort, and the ability of the business to create value for customers. This research employs a descriptive quantitative approach supported by BMC-based strategic analysis. The sample consisted of 100 customers of Warung Barokopi selected through purposive sampling. The criteria required respondents to have made at least one purchase within the last three months, to be at least 17 years old, and to be able to evaluate service and price based on their actual experience. Primary data were collected using a closed-ended questionnaire with a five-point Likert scale, while supporting data were obtained through direct observation and brief interviews with the business owner or manager. Data analysis was conducted through validity testing, reliability testing, descriptive analysis, and hypothesis testing by examining the relationship between service quality, price, and customer satisfaction. The results show that service quality has a positive and significant effect on customer satisfaction, with a path coefficient of 0.462, a t-value of 5.931, and a p-value of 0.000. Price also has a positive and significant effect on customer satisfaction, with a path coefficient of 0.381, a t-value of 4.722, and a p-value of 0.000. The R-square value of 0.617 indicates that service quality and price explain 61.7% of customer satisfaction. These findings confirm that customer satisfaction at Warung Barokopi is more strongly influenced by service quality, although it still requires support from fair, competitive, and value-based pricing. Based on the BMC analysis, the recommended strategies include strengthening value propositions, standardizing service procedures, developing price packages, optimizing social media channels, implementing customer loyalty programs, improving employee training, and managing customer relationships more sustainably. This study provides practical contributions for local culinary MSMEs in developing customer satisfaction strategies through a more structured and value-oriented business model.